The Study of Case-Based Learning Method in Intermediate Business Chinese Teaching - Liang, Yuping; Cojorn , Kantarat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This study aims to compare the spoken language communication abilities of students using traditional teaching methods versus case-based teaching methods. Additionally, it compares reading and writing abilities, as well as students' satisfaction with their instructors. The research targets a group of 40 international students at Guangxi Normal University who have completed a basic business Chinese language course. The research instruments include: 1. a 20-item spoken communication ability test, 2. a 20-item reading comprehension test, 3. a 10-item writing ability test, and 4. a 10-item student satisfaction questionnaire regarding their instructors. The statistical methods used in the study include percentages, mean scores, standard deviations, t-tests, and descriptive statistics. The study reveals the following results: 1. A significant difference at the 0.05 level was found between the spoken language communication abilities of students taught using traditional methods and those taught using case-based methods. The average score of students taught using the case-based method was higher; 2.A significant difference at the 0.05 level was observed in the reading abilities of students between the traditional and case-based teaching methods, with the average score for the case-based method being higher; 3. A significant difference at the 0.05 level was identified in the writing abilities of students between the traditional and case-based teaching methods, with the average score for the case-based method being higher; and 4. A significant difference at the 0.05 level was found in student satisfaction with their instructors between the two teaching methods, with the average satisfaction score being higher for the case-based method.